Awareness and Attitudes of Secondary School Students about Physiology Discipline in Southwest Region, Nigeria (Nigerian Journal of Physiological Sciences, 2022)
Physiology remains one of the core disciplines on which all biological and medical sciences were founded. In Nigeria, it is known that most students study Physiology at the undergraduate level by chance and not by choice and end up performing poorly, which could be mainly due to low awareness and knowledge of the discipline, its opportunities, and prospects. Therefore, this study investigated the awareness, attitude, and knowledge about physiology among senior secondary school students in Southwest Nigeria. A cross-sectional of 544 students in science-based senior secondary schools in south-west Nigeria were sampled. Our results showed a high level of awareness, with television being the dominant medium of information. However, knowledge of Physiology was low, while most of the students also showed interest in knowing more about it. Although gender does not seem to influence the level of knowledge, females had a better attitude towards learning about physiology. Similarly, residence did not affect attitude, howbeit associated with the level of knowledge. In conclusion, the high awareness and low knowledge observed in this study would give insights to educate students at the early stages of education about the opportunity and prospects of Physiology and other science-related disciplines.